Pulmonary Rehabilitation and Physical Activity in COPD - Tylczyńska, Natalia; Tylczyńska, Kinga; Skiba, Zuzanna; Skiba, Jakub; Zielińska, Aleksandra; Szypulski, Szymon; Kowalik, Kinga; Michalska, Maria; Iwaniuk, Sebastian; Maciejewski, Ignacy (Quality in Sport, 2025)
Introduction and Purpose: Chronic obstructive pulmonary disease (COPD) is a type of progressive lung disease characterized by chronic respiratory symptoms and airflow limitation. The purpose of this study was to present pathogenesis, symptoms, diagnosis and treatment of COPD and principal strategies and types of exercises of pulmonary rehabilitation in patients with COPD. Description of State of Knowledge: Chronic obstructive pulmonary disease (COPD) leads to progressive respiratory dysfunction, muscle loss, and decreased exercise capacity, significantly impairing quality of life. Pulmonary rehabilitation (PR) is a key non-pharmacological intervention, combining exercise training, education, and self-management to improve functional capacity and reduce symptoms. Various training modalities have demonstrated benefits in enhancing endurance, muscle strength, and quality of life in COPD patients. Individualized programs based on patient capacity and symptom burden are essential for optimizing rehabilitation outcomes. Conclusions: Pulmonary rehabilitation relieves dyspnoea and fatigue, improves emotional function and enhances the sense of control that individuals have over their condition. These improvements are moderately substantial and clinically significant. Rehabilitation serves as an essential component of the management of COPD and is beneficial in improving health-related quality of life and exercise capacity.